KEANEKARAGAMAN TUMBUHAN PAKU (PTERIDOPHYTA) DI KAWASAN WISATA AIR TERJUN KALIBENDO BANYUWANGI - Akbar, Haula Karima; Muhimmatin, Ifa; Nugrahani, Magdalena Putri (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Kalibendo Waterfall located in the plantation area of coffee, rubber, and clove in Kampunganyar Village, Banyuwangi Regency, Indonesia. The area has a height up to 825 meters with choppy topography, and a type B climate on the Schmidt-Ferguson scale so that it is a suitable environment for ferns (Pteridophyta). In the last five years, the Kalibendo waterfall area has been developed as a tourist area so that it can potentially affect the diversity of Pteridophyta. This research aims to study the diversity, abundance of species, and the importance index of Pteridophyta in the Kalibendo waterfall. This is a quantitative descriptive research with cruise methods along 650 meters and purposive sampling technique. Results of the study found 4 Ordo, 9 Families, and 20 Pteridophyta Species scattered in the ecosystem of clove, rubber, and river stands. The abundance of Pteridophyta individuals in the Kalibendo Banyuwangi waterfall tourist area was 1029 individuals. The species with the highest abundance value was Pyrrosia piloselloides with 389 individuals, and the lowest was Woodwardia radicans with 2 individuals. The fern species that had the highest importance index (INP) is Pyrrosia piloselloides as much as 53.67%, KR 37.85%, and FR 15.83%. The highest value of H' Pteridophyta is located in the river ecosystem. The highest value of E' Pteridophyta is located in the river ecosystem which shows an even distribution of species at that location. Kata kunci: air terjun, keanekaragaman, pteridophyta, wisata